User Representations in Human-Computer Interaction. Issue 5 (1st October 2021) - Seinfeld, Sofia; Feuchtner, Tiare; Maselli, Antonella; Müller, Jörg
ABSTRACT: Cursors, avatars, virtual hands or tools, and other rendered graphical objects, enable users to interact with computers such as PCs, game consoles or virtual reality systems. We analyze the role of these various objects from a user perspective under the unifying concept of "User Representations". These representations are virtual objects that artificially extend the users' physical bodies, enabling them to manipulate the virtual environment by performing motor actions that are continuously mapped to their User Representations. In this paper, we identify a set of concepts that are relevant for different User Representations, and provide a multidisciplinary review of the multisensory and cognitive factors underlying the control and subjective experience of User Representations. These concepts include visual appearance, multimodal feedback, sense of agency, input methods, peripersonal space, visual perspective, and body ownership. We further suggest a research agenda for these concepts, which can lead the human-computer interaction community towards a wider perspective of how users perceive and interact through their User Representations.